METHODOLOGY OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE IN THE NATIONAL RUSSIAN SCHOOL (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article examines current issues in the methodology of teaching Russian as a non-native language in school education.